Pengaruh Pelatihan Profesional, Penghargaan Finansial, dan Pertimbangan Pasar Kerja terhadap Minat Berkarir Akuntan Publik - Anita Norlaela; Muslimin Muslimin (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2023)
The number of public accountants in Indonesia is still relatively minimal, because accounting graduates have less interest in a career as public accountants. There are many factors that influence accounting graduates in choosing a career, including financial factors, training, and the job market. The purpose of this study was to examine and analyze the effect of professional training, financial rewards, and labor market considerations on public accountant career interests. The population in this study were Accounting S1 students from UPN